Ethnopsychological Peculiarities of Ratio Between Motivational-Meaningful Characteristics of Sociability in Latin American and Russian Students - O O Katchurina (Peoples' Friendship University of Russia (RUDN University), 2012)
The features of ratios between the motivational-meaningful characteristics of sociability of the Latin American and Russian students are analyzed in the article. The revealed distinctions in the ratios of the variables which determine the ethnopsychological specificity of sociability in the Latin American and Russian students are discussed.